Enhancement of university curriculum and secondary school education through utilisation of sustainable engineering and appropriate technology workshops - Loden, D.; Biswas, Wahidul (The Faculty of Engineering & Information Technology, University of Technology, Sydney, 2010)
Engineering faculties can struggle to find practical and meaningful tasks for students to undertake as part of their coursework whilst continuing to meet the broader requirements of Engineers Australia’s Professional Engineering Attributes. Engagement between university and secondary school curriculum through sustainable engineering and appropriate technology workshops developed by Engineers Without Borders Australia (EWBA) aims to address these challenges. This paper outlines EWBA’s new curriculum based initiative which provides university students with the opportunity to meaningfully engage with the broader community whilst educating secondary school students of the application of science to solve real world problems. The survey of teachers and secondary school students found that the program has effectively engaged secondary school students in what it means to be an engineer whilst surveys of university students has demonstrated that they have developed skills and knowledge aligned with the Engineers Australia’s Professional Engineering Attributes.